The Concept of Government Treasurer: Indonesia Case Study - Sumantri, Joko; Fuady, Muhammad Syahrul (Ilomata International Journal of Management, 2024)
The determination of the functional position of treasurer which combines the duties of the treasurer with the Commitment-Making Officer (PPK) and Payment Instruction Signing Officer (PPSPM) has blurred the function of "comptable" as part of the duties of the CFO (Chief Financial Officer) and "ordonateur" as part of the duties of COO (Chief Operational Officer). This paper seeks to answer research questions about how the functional position of treasurer should be defined so that it is in accordance with the intent of the State Treasury Law, the nature of the position, the order of professional responsibilities, and the family of positions. So that the position of treasurer becomes more in line with best treasury management practices. This research was conducted in the realm of financial management of the Indonesian state budget. By using qualitative descriptive research methods, we found that: the nature of the treasurer's work is expertise and independence, has extensive knowledge in the field of state financial management, behaves professionally, according to the law is responsible to the CFO, and the treasurer's field of duties needs to be made broader so that larger workload. The implications of this research are that the position of treasurer is more in line with the intent of the state treasury law, the scope of his duties adopts best practice treasury management, the nature of the work is more focused, and his career development is not hampered.